Lost in NYC : a subway adventure - Spiegelman, Nadja (TOON graphics., 2015)
On his first day going to a new school in New York City, Pablo has an adventure when he accidentally gets on the wrong subway train to go on the field trip to the Empire State Building. However, with the help of a new friend and from New York City itself, he finds his way again.